Адміністративно-правовий механізм запобігання корупції в органах поліції - Шинкаренко, Н. В.; Shinkarenko, N. V.; ORCID: http://orcid.org/0000-0002-4519-879X (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 209–215, 2016)
Розглянуто особливості правового регламентування та практики запобігання корупції в правоохоронних органах. Під адміністративно-правовим механізмом запобігання корупції в органах поліції розуміється система правових засобів, які дозволяють уповноваженим суб’єктам ефективно здійснювати діяльність із запобігання корупції в правоохоронних органах за допомогою заходів організаційно-правового характеру та заходів адміністративного примусу. Зроблено висновок, що для України важливим є розроблення цілісного адміністративно-правового механізму запобігання корупції.

Features of legal regulation and practices to prevent corruption in law enforcement agencies have been studied. Under administrative and legal mechanism to prevent corruption within the police agencies we understand the system of legal means that allow authorized entities to operate effectively to prevent corruption in law enforcement agencies with the assistance of measures of organizational and legal nature and administrative compulsion measures. The object of the research of this article is administrative and legal mechanism to prevent corruption within the police agencies of Ukraine. The objective of the study is to suggest new approaches to the prevention of corruption within the police agencies of Ukraine based on the study, analysis and compilation of legislation norms in the field of prevention of corruption, opinions of scholars on this issue and international and legal standards. According to the research, the author has concluded that mere legislative consolidation of the fundamental principles of preventing and combating corruption in the public and private spheres of social relations does not fully solve all the issues generated by the phenomenon of corruption. Practical implementation of the new anticorruption legislation is needed for overcoming corruption. It has been emphasized on the importance to develop integrated administrative and legal mechanism to prevent corruption in Ukraine.

Рассмотрены особенности правового регламентирования и практики предотвращения коррупции в правоохранительных органах. Под административно-правовым механизмом предотвращения коррупции в органах полиции понимается система правовых средств, которые позволяют уполномоченным субъектам эффективно осуществлять деятельность по предотвращению коррупции в правоохранительных органах с помощью мер организационно-правового характера и мер административного принуждения. Сделан вывод, что для Украины важна разработка целостного административно-правового механизма предотвращения коррупции.
Административно-правовой механизм предотвращения коррупции в органах полиции
Administrative and legal mechanism to prevent corruption within the police agencies
Шинкаренко, Н. В. Адміністративно-правовий механізм запобігання корупції в органах поліції / Н. В. Шинкаренко // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 209–215.
Шинкаренко Н. В. "Адміністративно-правовий механізм запобігання корупції в органах поліції." Вісник Харківського національного університету внутрішніх справ 4 (2016): 209-215.
Shinkarenko, N.V. (2016), “Administrative and legal mechanism to prevent corruption within the police agencies” [Administratyvno-pravovyi mekhanizm zapobihannia koruptsii v orhanah politsii], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 4, pp. 209–215.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; запобігання корупції; адміністративно-правовий механізм; антикорупційна політика; спеціальна перевірка; corruption; корупція; коррупция; prevention of corruption; administrative and legal mechanism; anti-corruption policy; special verification; National police of Ukraine; поліція; police; полиция; коррупция; предотвращения коррупции; административно-правовой механизм; антикоррупционная политика; специальная проверка; Национальная полиция Украины